Quantitative and Qualitative Characteristics (Phenotype) of Laying Ducks in Ternate City as the Basis for Local Livestock Breeding in North Maluku Province - Fatmona, Sariffudin; Utami, Sri; Putranti, Oktora Dwi (Agrikan Jurnal Agribisnis Perikanan, 2023)
Duck is a producer of animal protein whose production is eggs and meat, is a type of poultry that has the potential to be developed in the city of Ternate. However, until now there has been no characterization research in Ternate City. The aim of the study was to determine the phenotype characteristics as the basis for breeding local cattle in North Maluku. The materials used were adult male and female laying ducks, the variables observed were male ducks, qualitative characteristics were the character of coat color, beak color, eye color and quantitative characteristics were measured body size including femur length, tibia length, shank length, shank circumference, length wingspan, chest length, chest width, chest depth and hip width. calculating the mean formula, standard deviation and coefficient of diversity, qualitative characteristics of ducks using relative frequency analysis. The results showed that the quantitative characteristics of female ducks were more similar than those of male ducks. While the qualitative nature, the color is relatively the same both males and females have brown fur, only one is blackish brown, the skin color of the legs and beak is more dominantly black and brown compared to yellow, black yellow and brown yellow.